A 0.4 V, 12.2 pW leakage, 36.5 fJ/step switching efficiency data retention flip-flop in 22 nm FDSOI - Ji, Yuxin; Zhang, Yuhang; Chen, Changyan; Zhao, Jian; Rokhani, Fakhrul Zaman; Ismail, Yehea; Li, Yongfu (Institute of Electrical and Electronics Engineers, 2024)
Data-retention flip-flops (DR-FFs) efficiently maintain data during sleep mode, and retain state during transitions between active and sleep mode. This brief proposes an ultralow power DR-FF design with an improved autonomous data-retention (ADR) latch operating with a supply voltage range down to near/subthreshold, achieving a sleep mode leakage power of 12.2 pW, 1.4 × -3.8 × less than the prior CMOS DR-FFs. Our proposed DR-FFs consume the lowest active mode switching efficiency of 36.5 fJ/step, 1.2 × -4 × less than the prior works, and a comparable transition efficiency of 1.9 fJ/step. Furthermore, our proposed DR-FFs require minimal control signals, logic gates, and switches, significantly reducing design complexity, and avoiding the drawbacks of nonvolatile data retention FFs (NV-FFs).